2022
DOI: 10.3390/membranes12111031
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy Study of Albumin Interaction with Negatively Charged Liposome Membranes: Mutual Structural Effects of the Protein and the Bilayers

Abstract: Liposomes as drug carriers are usually injected into the systemic circulation where they are instantly exposed to plasma proteins. Liposome–protein interactions can affect both the stability of liposomes and the conformation of the associated protein leading to the altered biodistribution of the carrier. In this work, mutual effects of albumin and liposomal membrane in the course of the protein’s adsorption were examined in terms of quantity of bound protein, its structure, liposome membrane permeability, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Currently, there are no established guidelines for studying the liposomal protein corona, although many research groups have focused their attention on this subject. 3 , 16 , 38 , 75 , 76 Despite some well-described caveats, 77 centrifugation is currently the most used method for the separation of vesicle-protein assemblies from unbound proteins. 78 Thus, the following experiments and quantitative aspects relating to liposome–protein isolation through centrifugation are described with regard to the population of liposomes that are able to pellet upon centrifugation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no established guidelines for studying the liposomal protein corona, although many research groups have focused their attention on this subject. 3 , 16 , 38 , 75 , 76 Despite some well-described caveats, 77 centrifugation is currently the most used method for the separation of vesicle-protein assemblies from unbound proteins. 78 Thus, the following experiments and quantitative aspects relating to liposome–protein isolation through centrifugation are described with regard to the population of liposomes that are able to pellet upon centrifugation.…”
Section: Resultsmentioning
confidence: 99%
“…Kristensen et al also propose that albumin prefers to interact with liposomal hydrophobic domains, exposed through packing defects . Tretiakova et al, on the other hand, found that albumin adsorption on liposomes with various compositions primarily affects lipid polar headgroups by disrupting surface water hydrogen-bonding networks, leading to the formation of novel hydrogen bonds between lipid headgroups and the protein surface . Albumin adsorption to DMPC vesicles has also been described as being governed by electrostatic interactions by the work of Sabín et al, although hydrophobic interactions, mainly due to bilayer core penetration by the protein, are also acknowledged …”
Section: Introductionmentioning
confidence: 99%
“…Attenuated total reflectance (ATR)-FTIR spectrum of the co-loaded SOD1/enalaprilat CaP-particles covered with 5 kDa chitosan ( Figure 2 a) demonstrate the presence of all compounds—SOD1, enalaprilat and chitosan—within the particles. The incorporation of SOD1 and enalaprilat into CaP-particles resulted in a significant increase in the intensity in the regions of 1700–1600 cm −1 and 1600–1500 cm −1 , which can be attributed to the amide I and amide II of SOD1 [ 52 , 53 ] and vibrations of the aromatic structure of enalaprilat ( Figure 2 b,c). In addition, the inclusion of drugs in hybrid and CaP-particles was also evidenced by the intensity increase in the 1415–1375 cm −1 region, which can be attributed to the SOD1 and enalaprilat aromatic ring vibrations.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of CaP-particles with the chitosan “coat” is also clearly indicated by the dramatic intensity decrease in the 1260–1220 cm −1 region after particle covering. This is the main analytically significant band in CaP-particles—absorption band of the valent oscillations of the phosphate group (1220–1260 cm −1 ) [ 54 ], the main site of CaP-particles interaction with cationic groups of chitosan and the protein, SOD1 [ 53 , 54 , 55 ]. At the same time, the intensity of the absorption peak observed for CaP-particles at 950 cm −1 (corresponding to C⎯N bonds vibrations in chitosan [ 52 ]) increased as a result of chitosan covering, whereas the incorporation of SOD and enalaprilat into the particles resulted in a decrease in the intensity.…”
Section: Resultsmentioning
confidence: 99%
“…When exposed to serum or plasma, liposomes quickly adsorb large amounts of protein. Albumin, the most abundant negatively charged serum protein, binds to the surface of positively charged liposomes ( Tretiakova et al, 2022 ). Liposomes that bind to plasma proteins act as an opsonin, promoting specific interactions with receptors on macrophages or hepatocytes, thereby increasing liposome uptake by these cells ( Yan et al, 2005 ).…”
Section: Designing Nanocarrier Liposomes For Drug Deliverymentioning
confidence: 99%